Pengaruh Pemberian Air Gula Merah Terhadap Kebugaran Jasmani - Rani Rahmasari Tanuwijaya; Agus Kristiyanto; Muchsin Doewes (Jurnal Gizi, 2017)
Endurance athletes are required to consume beverages containing electrolytes and carbohydrates during and after exercise or during the match. Palm sugar is also one type of natural sugar that contains glucose and fructose and has a low glycemic index. The type and design of this research was true experimental research with double blind. The experiment in this research is 2 groups, group of jogging with brown sugar water and group of jogging with plainmineral water with a sample of 32 people who are members of Spiji Football Club. This study was conducted in April 2007. The results obtained that the jogging exercise with brown sugar water and plain mineral water have an effect to improve the physical fitness of students offootball club. Based on data analysis, it can be seen that jogging exercise with brown sugar water treatment with mean equal to 3,54, this is higher than jogging with plainmineral water which was 2,94. Based on result of unpaired T test it was obtained result of significance as p = 0,123 which mean that it has no significant difference. Jogging exercise with brown sugar water intake can improve physical fitness higher than jogging practice with plainmineral water but has a insignificant difference Keywords: carbohydrate drinks; brown sugar water; physical training; physical fitness